Pengaruh Dosis Bokashi Serbuk Gergaji terhadap Pertumbuhan dan Hasil Tanaman Mentimun Jepang (Cucumis sativus L.) pada Tanah Gambut - Yulianti Hidayah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2013)
Peatlands have the potential to be used as agricultural development even though a number of obstacles are encountered, such as the chemical, physical and biological characteristics of the soil. Chemical constraints such as low pH, high C / N ratio, low P, K, Ca and Mg content. Efforts to increase soil pH and soil fertility by fertilizing. Bokashi is an organic fertilizer made using effective microorganism technology. The aim of the study (i) is to know the effect and (ii) to get the best dosage of sawdust bokashi on the growth and yield of Japanese cucumber plants on peat soil. Implemented in the Greenhouse Faculty of Agriculture Unlam Banjarbaru in March - June 2002, using a single Randomized Complete Design (CRD) factor. The factors studied were the treatment of sawdust bokashi dose (B) as many as seven levels, namely b1 = 2.5 t.ha - 1, b2 = 5 t.ha - 1, b3 = 7.5 t.ha -1, b4 = 10 t.ha -1 and b5 = 12.5 t.ha -1, b6 = 15.0 t.ha-1, b7 = 17.5 t.h-1. The variables observed were plant height aged 14, 21, 28, 35 and 42 days after planting (DAP), the age of the first flowering, when the first fruit was formed, at the first harvest, fruit length, fruit diameter, number of fruits per plant and weight per fruit. plant. The treatment had no effect on plant height variables at ages 14, 21, 28, 35 and 42 DAP, when the first flowering, when the first fruit was formed, at the first harvest, fruit diameter and number of fruits per plant. But the treatment affected the fruit weight per plant and fruit length, with the best treatment 12.5 t.ha-1 yielding the best fruit weight per plant and fruit length.